INVESTIGATIONS OF FORMATION OF PHYTOPLANKTON COMMUNITY IN THE ARPA RIVER (ARMENIA) AND ITS MAIN TRIBUTARIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
A modern study of the Arpa River and its tributaries allows evaluating the ecological state of the ecosystem according to phytoplankton development indicators and comparing it with previous data. It is known that modified control of hydrosystems for hydropower stations changes quantitative and qualitative indicators of water, which increases anthropogenic impact on the diversity of hydrobionts. In order to mitigate the environmental risks and improve the ecosystem self-cleaning it is necessary to carry out continuous monitoring and rapid assessment of the change in the composition of microalgae indicators.
Keywords: phytoplankton, cyanobacteria, saprobity level, index of biodiversiti